Achieving high diversity and multiplexing gains in the asynchronous parallel relay network. Issue 2 (12th February 2013) - Dai, Mingjun; Wan Sung, Chi
ABSTRACT A single source‐destination pair communicating via a layer of parallel relay nodes under quasi‐static slow fading environment is investigated. The time delays from the source to the destination via different relays are assumed to be different. For such an asynchronous environment, a new transmission scheme is constructed so as to achieve better diversity‐multiplexing tradeoff (DMT). More specifically, both the source and the destination adopts orthogonal frequency division multiplexing technique to solve the asynchronous problem; the relays cooperatively apply the distributed generalised complex orthogonal design, a form of orthogonal space–time coding, for high‐rate transmission. Each relay is assumed to use the adaptive amplify‐and‐forward relaying strategy. To optimise its outage performance, a distributed on‐off power control rule applied to the relays is analytically derived and is proved to yield full spatial diversity order. Compared with an existing protocol, our proposed scheme is shown to achieve the same DMT when there are four relay nodes and better DMT when there are more. Besides, the DMT gap between our scheme and the existing one increases with the number of relay nodes. Copyright © 2013 John Wiley & Sons, Ltd.